2015
DOI: 10.1096/fj.14-267195
|View full text |Cite
|
Sign up to set email alerts
|

The clock protein period 2 synchronizes mitotic expansion and decidual transformation of human endometrial stromal cells

Abstract: Implantation requires coordinated interactions between the conceptus and surrounding decidual cells, but the involvement of clock genes in this process is incompletely understood. Circadian oscillations are predicated on transcriptional-translational feedback loops, which balance the activities of the transcriptional activators CLOCK (circadian locomotor output cycles kaput) and brain muscle arnt-like 1 and repressors encoded by PER (Period) and Cryptochrome genes. We show that loss of PER2 expression silences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 61 publications
1
25
1
Order By: Relevance
“…When this downregulation is premature, the decidual response is disorganized. In fact, endometrial biopsies during the midluteal phase from patients with recurrent miscarriages demonstrated an inverse correlation between Per2 transcript levels and number of failed pregnancies [77]. These findings suggest that intact circadian timing of reproductive events subsequent to ovulation may be required for successful conception.…”
Section: Embryo Implantation and Early Gestationmentioning
confidence: 89%
See 1 more Smart Citation
“…When this downregulation is premature, the decidual response is disorganized. In fact, endometrial biopsies during the midluteal phase from patients with recurrent miscarriages demonstrated an inverse correlation between Per2 transcript levels and number of failed pregnancies [77]. These findings suggest that intact circadian timing of reproductive events subsequent to ovulation may be required for successful conception.…”
Section: Embryo Implantation and Early Gestationmentioning
confidence: 89%
“…Bmal1 and Per2 expression have been demonstrated in both the non-pregnant and gravid uterine myometrium in women [15]. More relevant for fertility is the recent finding that Per2 is also rhythmically expressed in the human endometrial stromal cells of the uterus and its expression is downregulated during decidualization [77]. When this downregulation is premature, the decidual response is disorganized.…”
Section: Embryo Implantation and Early Gestationmentioning
confidence: 99%
“…Several studies have documented that the transformation of endometrial stromal cells into specialized decidual cells is perturbed RPL . Collectively, the data indicate that the endometrium in affected women is characterized by a disordered and prolonged pro‐inflammatory decidual response .…”
Section: The Alternative Rpl Paradigm: the ‘Implantation Checkpoint’ mentioning
confidence: 92%
“…However, decidual cells are programmed to resist a range of environmental stress signals, thus critical ensuring that the pregnancy survives this transitional period. Several molecular pathways have been identified that underpin decidual stress resistance, including silencing of circadian gene expression, inhibition of stress pathways such as c‐Jun N ‐terminal kinase, attenuated inositol trisphosphate signaling, global cellular hypoSUMOylation, downregulation of the metabolic stress enzyme O‐linked N ‐acetylglucosamine (GlcNAc) transferase, resistance to miRNA‐mediated gene silencing through loss of argonaut proteins, and marked upregulation of free radical scavengers . By silencing multiple pathways, decidual cells prioritize cellular homeostasis over an adaptive response to stress signals.…”
Section: The Alternative Rpl Paradigm: the ‘Implantation Checkpoint’ mentioning
confidence: 99%
“…Moreover, the clock protein PER2 synchronizes mitotic expansion and decidual transformation of human endometrial stromal cells [55]. In Taiwan, promoter methylation in the PER1, PER2, or CRY1 clock genes was detected in about onethird of endometrial cancers and one-fifth of noncancerous endometrial tissues of thirty-five paired specimens indicating disruption of the biological clock in the development of endometrial cancer [56].…”
Section: Archives In Cancer Researchmentioning
confidence: 99%